Decreasing Radiation Exposure in Pediatric Clavicle and Metatarsal Fractures: A QI Initiative. Issue 3 (15th March 2021) - Brown, Zoe; Perry, Michael; Wozniak, Amy W.; Cappello, Teresa
Abstract : Background: Protecting the pediatric population from unnecessary medical radiation is an important public health initiative. Efforts have been made to reduce radiation exposure in the treatment of pediatric fractures without compromising quality of care. Using a standardized protocol for imaging of pediatric clavicle and metatarsal fractures is a reliable method for reducing pediatric radiation exposure in the management of these fractures. Methods: In the year 2015, the senior author altered follow-up imaging practices for 2 common pediatric fractures: metatarsal and clavicular. Initial radiographic evaluation included the standard 3 views for metatarsal fractures and 2 views for clavicle fractures. This standard diagnostic procedure remained constant throughout the study. Follow-up x-rays from 2009 to 2014 routinely included 3 views of the foot and 2 views of the clavicle. The protocol was changed and from 2016 to 2019, follow-up x-rays for fractures routinely included 2 views of the foot and 1 view of the clavicle, thereby decreasing the number of x-rays utilized to manage these fractures. Results: There was a significant reduction in the number of clavicle x-rays ( P <0.001) and metatarsal x-rays ( P =0.004) taken in follow-up between the time-periods. Median values for metatarsal views decreased by 1, matching the adjustment in protocol. In addition, the vast majority of clavicle fractures (90.80%) were managed with 1 follow-up view in 2016 to 2019 compared with 2 views (72.48%) from 2009 to 2014. Conclusions: This study achieved a reduction in radiation exposure in pediatric patients with nonoperatively managed clavicle and metatarsal fractures. Improving the quality of care of patients through decreasing the number of x-rays taken protects individuals from adverse side effects, as well as offers various public health benefits in terms of reduction in expenditures. Level of Evidence: Level III—retrospective comparative study.